ADAPTATION OF TEACHER’S RELATIONAL COMPETENCE SCALE IN THE CONTEXT OF TEACHERS OF GUIDANCE AND COUNSELING - Hotifah, Yuliati; Nawangsari, Nur Ainy Fardana; Yoenanto, Nono Hery (Jurnal Psikologi, 2022)
This research aims to adapt the teacher relational competence scale by Vidmar and Kerman (2016) to the Indonesian language and culture, especially in the context of guidance and counseling teachers. The adaptation process has used the International Test Commission Guidelines. This adaptation involves 276 subjects with criteria: guidance and counseling teachers with a minimum working period of 5 years and who have attended professional teacher education (Pendidikan Profesi Guru). There are four research instruments, namely TRCS, linguist evaluation form, content expert evaluation form, and pilot studyassessment form. The data analysis technique uses content analysis and constructs analysis. Content analysis has used the content validity index (CVI), while construct analysis has used confirmatory factor analysis(CFA) with AMOS version 22. Reliability test based on homogeneity (internal consistency) using Cronbach’s Alpha coefficient. The analysis of evidence based on test content contained ten items with a mean score of 0.60. The results of the evidence-based construct analysis using CFA obtained 17 items with a loading factor > .50. The reliability coefficient with Cronbach’s alpha is .933. So that in the future, only 17 items will be used as a measure of the Indonesian version of the Relational Competence Scale for guidance and counseling teachers.